Influence of the elicitors on the accumulation of secondary metabolites and antioxidant activities in the Polyscias fruticosa (L.) Harms in vitro roots - Le, Thi Van Anh; Tran, Ngoc Trung Anh; Duong, Phuong Anh; Bao Chau, Ha Tran; Dinh, Thi Hien Diu; Mai, Nga Thi Phuong (Academia Journal of Biology, 2024)
Polyscias fruticosa (L.) Harms, belonging to the Ginseng family (Araliaceae), is a valuable medicinal plant in Vietnam. Recognized in the Vietnamese Pharmacopoeia, it is esteemed for its antioxidant, anti-inflammatory, and antipyretic properties, making it a significant contributor to traditional medicine. This research contributes to the understanding of elicitor-induced changes in antioxidant activity, and secondary metabolite content of in vitro root extract of P. fruticosa. The results showed that the antioxidant activity of the root extract tested by DPPH radical scavenging assay with an IC50 value of 1.28 mg/mL in the baseline and the lowest IC50 value of 0.89 mg/mL in the medium treated with yeast extract (YE). The highest total phenolic and flavonoid content were displayed in jasmonic acid-treated samples at 24.31 ± 2.86 mg gallic acid/g extract and 29.25 ± 0.26 mg quercetin/g extract, respectively. The highest saponin was also produced in roots elicited by jasmonic acid, where it reached about 167.19 ± 3.29 mg aescin/g extract. Furthermore, investigation with antioxidant enzyme activities showed another superiority when using elicitors YE (64.4 ± 3,14 U/mg protein) and mannitol (Man) (65.39 ± 3.85 U/mg protein) in peroxidase (POD) activity and using jasmonic acid (8.87 ± 0.74 U/mg) in catalase (CAT) activity. Lastly, TPC and TFC exhibited a positive correlation of r = 0.53 while the TPC and DPPH scavenging activity and TFC and POD showed a remarkably negative correlation of r around -0.8. In conclusion, this study highlights the advancements in eliciting root cultures to enhance specific phytochemicals and antioxidant activity. The information provided holds significant value and will be of interest to scientists engaged in plant biotechnology, particularly in the elicitation of medicinal plant roots.